Industrial Waste Treatment Management: A Review - Elkana Timotius; Galuh Sukmarani (Widyagama University of Malang, 2021)
Industrial development is hand-to-hand with economic growth. It has a positive impact on many economic sectors and human living, but also produces hazardous waste which giving a negative impact on the environment and human health. Industrial wastes have a high contribution to climate changes, many human diseases, a mutation on animals and plants. Recently, there are many methods to overcome industrial waste include physical, chemical, and biological treatment. Moreover, waste management also is developed to optimize the treatment using 3R (Reduce, Reuse, and Recycle) and WTE (Waste to Energy). Therefore, this paper tried to discuss many technologies for industrial waste treatment and management includes recent research, benefit, and drawback.